“Ofo" in Cultural Identity and Spiritual Practice in Owa Culture - Ikechukwu Monday Osebor (Methexis)
The Ofo is a cultural artifact deeply rooted in the traditions of the Owa people, part of the Ika-Igbo nation in Delta State, Nigeria. It represents personal accomplishment, power, and individual success, often associated with the male's personal deity or "Chi" (God). The Ofo is typically a wooden staff, carved from a specific type of tree believed to have spiritual significance, serving both spiritual and social functions. The wood is usually polished and may be adorned with symbols or decorations. It often features intricate carvings, including anthropomorphic figures, animals, or geometric patterns. These carvings are not merely decorative but hold symbolic meanings related to the owner's lineage, status, or spiritual beliefs. This symbolic image is, however, challenged by globalization, preservation of sacred objects, and cultural interpretation to make contemporary relevance pose several challenges. This study maintains that the teaching and learning of the ethics of artifacts in our schools would be educational tools, allowing people to learn about the moral protection of artifacts, aesthetic utility, and harms to the environment. The implementation of the ethics of artifacts would encourage the use of conservation and application of techniques to preserve and restore artifacts. This includes chemical treatments, environmental controls, and physical repairs to learn more about the sacred objects and their importance in our environment.